2010
DOI: 10.1186/1758-2652-13-21
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between PEPFAR funding and improvement in national health indicators in Africa? A retrospective study

Abstract: BackgroundThe US President's Emergency Plan for AIDS Relief (PEPFAR) was reauthorized in June 2008 with a three-fold increase in funds, and a broader, more explicit mandate to improve health in the low- and middle-income countries that it funded. However, the ability of a disease-specific, or vertical, programme to have a spill-over effect and improve health outcomes has been questioned. In this study, we sought to examine associations between being designated as a PEPFAR focus country (and receiving increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 16 publications
2
40
1
Order By: Relevance
“…Also, an ideological struggle seems to have arisen around whether GHIs have de facto strengthened health systems or had the opposite effect [44-48]. Answers to these questions will influence future HSS directions for GHIs and countries and caution is needed in interpreting them, since answers might differ depending on who the assessor is and what meaning is given to “HSS”.…”
Section: Discussionmentioning
confidence: 99%
“…Also, an ideological struggle seems to have arisen around whether GHIs have de facto strengthened health systems or had the opposite effect [44-48]. Answers to these questions will influence future HSS directions for GHIs and countries and caution is needed in interpreting them, since answers might differ depending on who the assessor is and what meaning is given to “HSS”.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ability of disease-specific program like PEPFAR or Global Fund to have a spill-over effect and improve health outcomes has been questioned. Duber et al found that vertical programs, even on the scale of PEPFAR, may not impact health outcomes that were not specifically targeted on a national level [12]. Attempts have been made to integrate donor-funded HIV prevention, care, and treatment programs into national health systems to ensure efficiency and sustainability, including: TB [13••, 14], maternal-child health (MCH) [15–20], cervical cancer screening [21], sexually transmitted infection (STI) [16, 22], and family planning [23, 24] programs.…”
Section: Introductionmentioning
confidence: 99%
“…A few years later, President George W. Bush of the United States (US) introduced PEPFAR, the largest bilateral programme for a single disease to date. 3 Of PEPFAR's original priority countries, 12 out of 15 were in Africa. The United Nations also scaled-up its response, through the Joint UN Programme on HIV/AIDS (UNAIDS), involving an increasing number of co-sponsoring agencies.…”
Section: Introductionmentioning
confidence: 99%